2015
DOI: 10.1016/j.psyneuen.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 2C receptor contributes to gender differences in stress-induced hypophagia in aged mice

Abstract: The combination of depression and anorexia may influence morbidity and progressive physical disability in the elderly. Gender differences exist in hypothalamic-pituitary-adrenal axis activation following stress exposure. The objective of this study was to investigate gender differences in feeding behavior under novelty stress in aged mice. Food intake measurement, immunohistochemical assessment, and mRNA expression analysis were conducted to investigate the role of serotonin 2C receptor (5-HT(2C)R) and its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…The administered dose of RKT is approximately equivalent to a typical clinical dose when converted based on body surface area (as recommended by the FDA) and this dose has previously been reported to show ameliorative effects in a mouse model of anorexia13144041. Cumulative food intake was determined at 1, 3 and 6 h after stress exposure.…”
Section: Methodsmentioning
confidence: 99%
“…The administered dose of RKT is approximately equivalent to a typical clinical dose when converted based on body surface area (as recommended by the FDA) and this dose has previously been reported to show ameliorative effects in a mouse model of anorexia13144041. Cumulative food intake was determined at 1, 3 and 6 h after stress exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Ghrelin, a hormone produced in the peripheral organs and central nervous system, is known to be involved in the regulation of appetite, gastrointestinal motility, and growth hormone release. Recently, the abnormal kinetics of ghrelin due to stress loading have been reported [ 1 3 , 9 , 10 ]. Intracerebroventricular administration of CRF or exposure to psychological stress suppresses food intake in association with decreases in peripheral ghrelin levels during fasting [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the abnormal kinetics of ghrelin due to stress loading have been reported [ 1 3 , 9 , 10 ]. Intracerebroventricular administration of CRF or exposure to psychological stress suppresses food intake in association with decreases in peripheral ghrelin levels during fasting [ 1 , 3 ]. In ghrelin deficienct conditions, the administration of exogenous acylated ghrelin or the endogenous ghrelin enhancer rikkunshito clearly recovers the effect of stress-induced hypophagia [ 1 4 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…RKT (0.5 g/kg) or vehicle (distilled water, 4 ml/kg) was given daily by orogastric gavage for 7 days, and on day 8, at 6 h and 1 h before the abdominal surgery that took place at 1–2 h before the dark phase. The last RKT treatment before surgery was to maintain the effect based on previous studies showing that RKT administered at 1 h before novelty stress in mice improves feeding [ 26 28 ]. Non-surgery controls remained in their home cages.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we demonstrated that RKT blocked L-dopa-inhibited gastric emptying in rats [ 25 ]. RKT can also restore novelty stress-induced reduction of food intake in mice [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%